2005
DOI: 10.4315/0362-028x-68.12.2631
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Consumer Food Safety Knowledge and Reported Behavior among Students from Health Sciences in One Region of Spain

Abstract: A survey was conducted to investigate the relationship between knowledge about food safety and actual food handling practices among Spanish university students (mainly from the health sciences disciplines) who usually prepare meals at home. Based on level of education in food safety topics, students were divided in three groups: high, which included students from Food Science and Nutrition; medium, which included students from other health sciences; and low, which included students from non-health-related stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 6 publications
8
43
1
1
Order By: Relevance
“…This difference could be due to the fact that Salmonella is the pathogen involved in most outbreaks of foodborne illness in Jordan in the past few years. Similar finding was discovered by Garayoa et al (2005) who found that proportion of Spanish university students correctly identified the food vehicle for transmission of Salmonella was greater than those who identified the food vehicle for transmission of S. aureus, Clostridium botulinum, L. monocytogenes and Trichinella. Low personal perception of food safety reported by female college students live in dorms in north of Jordan likely contributes, at the short term, to their decision to consume risky foods which may affect students' susceptibility to foodborne illness and contributes, at the long term, to foodborne illnesses in the home as this target group is future mothers and food preparers.…”
Section: Variablesupporting
confidence: 79%
See 3 more Smart Citations
“…This difference could be due to the fact that Salmonella is the pathogen involved in most outbreaks of foodborne illness in Jordan in the past few years. Similar finding was discovered by Garayoa et al (2005) who found that proportion of Spanish university students correctly identified the food vehicle for transmission of Salmonella was greater than those who identified the food vehicle for transmission of S. aureus, Clostridium botulinum, L. monocytogenes and Trichinella. Low personal perception of food safety reported by female college students live in dorms in north of Jordan likely contributes, at the short term, to their decision to consume risky foods which may affect students' susceptibility to foodborne illness and contributes, at the long term, to foodborne illnesses in the home as this target group is future mothers and food preparers.…”
Section: Variablesupporting
confidence: 79%
“…Most of the studies that examined food safety knowledge of young adults discovered, as this study did, that food safety knowledge of young adults is at an insufficient level Garayoa et al, 2005;Sanlier, 2009;Sharif & AlMalki, 2010;Unklesbay et al, 1998). Sanlier (2009) reported that food safety knowledge score of young consumers in Ankara, Turkey was of 5.81 out of 10 points.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, Morrone & Rathburn, (2003) and Unklesbay et al (1998) found that only a few studies have been conducted to explore the food safety knowledge, and behaviours among college students in developed country. Unusan (2007) and Garayoa et al (2005) found significant difference among education levels concerning attitude towards food safety and knowledge. According to Shepherd (1989) numerous variables influence consumer's knowledge and behaviours processes.…”
Section: Introductionmentioning
confidence: 91%